The role of family counseling in handling economic problems and family harmony - Aryani, Eka; Gusdian, Putri Milenia; Pasaribu, Sri Melati (Universitas Negeri Yogyakarta, 2025)
Family economic problems represent a critical factor that can disrupt household harmony and overall well-being. Financial stressors such as income instability, debt, lack of financial management skills, and differing financial values may undermine communication, intensify conflict, and diminish emotional support among family members. This study aims to explore the role of counselors in addressing economic challenges within families and fostering harmony through family counseling. Employing a qualitative approach, data were gathered to capture in-depth perspectives on the impact of economic issues and the interventions provided. Family counseling is viewed as a process that engages all members in identifying problems, enhancing communication, and developing mutually beneficial solutions. Counselors utilize various approaches, including systemic family therapy, narrative methods, and cognitive-behavioral techniques, while integrating financial planning and collaborating with financial experts when necessary. Findings indicate that effective counseling interventions contribute to increased family resilience, improved emotional stability, and strengthened interpersonal relationships, even in the context of severe economic strain. This study underscores the importance of combining psychosocial support with financial guidance to restore harmony, maintain stability, and promote a cohesive, supportive family environment.